2022
DOI: 10.1371/journal.pone.0270906
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Comments on hair disorders associated with dupilumab based on VigiBase

Abstract: Background Dupilumab is a human antibody that blocks the signaling of both interleukin-4 and interleukin-13 receptors. It has been approved for the treatment of moderate-to-severe atopic dermatitis. However, several case reports have reported conflicting effects of dupilumab on alopecia. Objectives This study aimed to examine dupilumab-related hair disorders using the large real-world database, VigiBase. Methods All individual case safety reports associated with dupilumab in the Uppsala Monitoring Center V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…A study using the VigiBase, a real-world pharmacovigilance database concluded that hair disorders corresponded to 2.2% of total dupilumab adverse events. This study concluded that dupilumab was associated with both hair growth and loss and overall, the paradoxical results of dupilumab in hair disorders might be caused by complex disease factors, such as IgE and IL-4 levels and the complexity of AA pathogenesis 14 .…”
Section: Financing Informationmentioning
confidence: 77%
See 1 more Smart Citation
“…A study using the VigiBase, a real-world pharmacovigilance database concluded that hair disorders corresponded to 2.2% of total dupilumab adverse events. This study concluded that dupilumab was associated with both hair growth and loss and overall, the paradoxical results of dupilumab in hair disorders might be caused by complex disease factors, such as IgE and IL-4 levels and the complexity of AA pathogenesis 14 .…”
Section: Financing Informationmentioning
confidence: 77%
“…However, the relationship between dupilumab and alopecia areata remains controversial as some patients experience improvement after starting treatment while others develop dupilumab-induced alopecia 13 with some studies suggesting that Th2 inhibition may amplify alternate pathways such as Th1 and Th17 resulting in hair loss 14 . Moreover, alopecia associated with dupilumab tends to follow an androgenetic pattern and usually has an eczematous pattern upon histopathological examination 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Hair loss is listed among the side effects in the omalizumab package insert, but unlisted for the other study drugs. Several published case reports and a previous analysis based on VigiBase considered the potential correlation between the onset of hair disorders and dupilumab therapy [ 62 64 ]. Nevertheless, a paradoxical effect of dupilumab as a beneficial treatment for alopecia areata has been reported [ 65 ].…”
Section: Discussionmentioning
confidence: 99%